PENETAPAN KADAR FLAVONOID TOTAL EKSTRAK ETANOL DAUN TANAMAN JONGI (Dillenia serrata) MENGGUNAKAN METODE SPEKTROFOTOMETRI UV-VIS - Ananda, Savitri; Pratama, Mamat; Baits, Muzakkir (Makassar Pharmaceutical Science Journal (MPSJ), 2023)
Jongi leaves (Dillernia serrata) is a type of medicinal plant which is used as an anti-inflammatory, antioxidant, antimicrobial, antitumor, anti-ulcer, immunoprevention, cancer chemoprevention, medicine for thrush, vomiting blood, fever, and wound medicine because it contains polyphenolic compounds, such as tannins and flavonoids. This study aims to determine the total flavonoid content of jongi leaves (Dillenia serrata) using the UV-VIS spectrophotometry method. This type of research is laboratory experimental using a spectrophotometer method based on the determination of extract levels and quarcetin standards. The stages of this research began with sample preparation, qualitative testing of flavonoid compounds, and ended with the determination of total flavonoid content of the sample and quarcetin standard. This study obtained results that positive jongi leaf extract contained flavonoids based on the results of identification using FeCl3 reagents and on the results of quantitative testing using UV-VIS spectrophotometry jongi fruit extract had a percentage of flavonoid content of 16.8633%.